TINJAUAN GENDER IDENTITY - RESPON DAN PERSEPSI TERHADAP IKLAN TELEVISI - Whidya Utami (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2004)
This paper seeks lo challenge the tendency lo represent gender as a unitary theoretical construct, and would argue for a more di.fjerentiated view of how the psychological aspect of gender influence the perception of advertising This paper use a small-scale exploratory study to examine the potential impact o,f'gender identity within consumer' self - schemas on their perception of advertising. Bern's ,)'ex Role Inventory (SRI) was administered to 20 young adults who then watched video clips of television advertisements. The focus group discussions about the advertisements were analyzed within the context of the respondents ' gender schemas identified via the Bern SRI score: masculine. feminine, androgynous or und(tferentiated. The centrality of gender identity to self-schemas affected how consumers processed and interpreted the advertising. This provides support for a more differentiated approach to representing men and women within gender research and advertising.